Panoramic view of Dawson from the Midnight Dome, Yukon Territory, Sept. 2, 1900. - Goetzman, H. J.
Caption on image: "Dawson from the mountain top. Sept. 2 1900" PH Coll 246.45 [Meed journal: "Dawson, Y.T. from mountain top, Sept 2, 1900.Situated at confluence of Klondike River and the Yukon River. Looking upstream. Floating near shore are rafts of cordwood for fuel in winter."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number